2020
DOI: 10.3390/antiox9040317
|View full text |Cite
|
Sign up to set email alerts
|

Regular Intake of Pistachio Mitigates the Deleterious Effects of a High Fat-Diet in the Brain of Obese Mice

Abstract: Obesity has been associated with neurodegeneration and cognitive dysfunctions. Recent data showed that pistachio consumption is able to prevent and ameliorate dyslipidemia, hepatic steatosis, systemic and adipose tissue inflammation in mice fed a high-fat diet (HFD). The present study investigated the neuroprotective effects of pistachio intake in HFD mice. Three groups of mice were fed a standard diet (STD), HFD, or HFD supplemented with pistachio (HFD-P) for 16 weeks. Metabolic parameters (oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…Consistent with this, free radical scavengers such as SOD and aconitase were significantly decreased, which most likely exerted a negative impact on mitochondrial function as evidenced by a significant reduction in mitochondrial state 3 respiration in maximal respiration capacity. These results are in agreement with the increased superoxide production and swelling—an indicator of permeability transition pore—selectively in the mitochondria within the cortex of mice fed a HFD for 16 weeks [ 44 ]. Although these studies do not establish a clear link between mitochondrial defects specifically in the prefrontal cortex and obesity, other investigators have demonstrated similar results in this specific brain area.…”
Section: Mitochondrial Dysfunction In the Cnssupporting
confidence: 82%
“…Consistent with this, free radical scavengers such as SOD and aconitase were significantly decreased, which most likely exerted a negative impact on mitochondrial function as evidenced by a significant reduction in mitochondrial state 3 respiration in maximal respiration capacity. These results are in agreement with the increased superoxide production and swelling—an indicator of permeability transition pore—selectively in the mitochondria within the cortex of mice fed a HFD for 16 weeks [ 44 ]. Although these studies do not establish a clear link between mitochondrial defects specifically in the prefrontal cortex and obesity, other investigators have demonstrated similar results in this specific brain area.…”
Section: Mitochondrial Dysfunction In the Cnssupporting
confidence: 82%
“…Although we did not investigate the effects of lemon IntergroPectin on Gal-3 regulation, oxidative stress and neuroinflammation inhibition in primary neurons and glial cells (or on animal model of brain disorders), our preliminary observations on neuroblastoma cells suggest the applicative potential of these new bioactive extracts in the treatment of complex neurological pathologies. Numerous literature data reveals that many other natural biomolecules exhibit neuroprotective effects [ 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several phytochemical complexes with antioxidant function have been identified as potential therapeutic agents to prevent/treat neurodegeneration disorders [ 4 , 5 , 6 , 7 ]. Specifically, the ingestion of foods with high antioxidant power, such as nuts, can prevent neuronal dysfunctions during obesity [ 8 ].…”
mentioning
confidence: 99%